2012
DOI: 10.5539/ijbm.v7n2p150
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of eCRM on Loyalty and Retention of Customers in Iranian Telecommunication Sector

Abstract: The research approach is to appraise the impact of electronic customer relationship management in creating loyalty and retention of customers in Iran mobile telecommunication sector. 200 customers who use Iranian mobile telecom operators' services (Hamrah-e Avval , Irancell, and Taliya) have been asked as respondents in this research. The objective of this study is to find the relationship between eCRM effective factors and loyalty and retention factors in order to conduct the Iranian mobile telecom operators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The zakah organization should identify the key needs of muzakki then the services given by personnel will be match with muzakki's willing. The structure of the strategy should be based on flexibility and explicitly of the policies especially policies of taking fund and its cost (Abdolhosseini, et al, 2012). All these both of personnel 's behavior and business process must be supported by a good updating of technology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The zakah organization should identify the key needs of muzakki then the services given by personnel will be match with muzakki's willing. The structure of the strategy should be based on flexibility and explicitly of the policies especially policies of taking fund and its cost (Abdolhosseini, et al, 2012). All these both of personnel 's behavior and business process must be supported by a good updating of technology.…”
Section: Resultsmentioning
confidence: 99%
“…The finding shows that behavior of the employees is significantly relate and contribute to customer satisfaction and loyalty. Therefore, (Abdolhosseini, et al 2012) investigated the impact of CRM on customer loyalty and retention in the telecom industry in Iran and found that commitment and vision of the management system is highly required for a successful CRM implementation. Moreover, study by (Kurniati et.al.…”
Section: Introductionmentioning
confidence: 99%
“…Nambiar et al (2019), in their study, showed that customer value has positive impact of customer retention. A gamut studies emphasized to seek out the connection between Electronic Customer Relationship Management’s (e-CRM's) effective factors, loyalty and customer retention (Khan & Shahzad, 2012; Abdolhosseini Khaligh et al, 2012). Sandes and Urdan (2013), in their study, also verify eWOM’s effects on consumer behaviour and its impact on brand image but has a negligible impact on the purchase intention of the consumer.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Then it must also allow access to user systems through various client systems such as personal digital assistants (PDAs), personal computers and mobile phones. Khaligh et al (2012) described many opportunities for using e-CRM in marketing for companies. Such as increased interaction and relationships between customers by offering options in personalization, which all options are a source of competitive advantage.…”
Section: Literature Review On E-crmmentioning
confidence: 99%